Piezoelectric biosensor for the determination of Tumor Necrosis Factor Alpha - Pohanka, Miroslav (Talanta, 2018)
Tumor Necrosis Factor Alpha (TNFα) is an important marker of inflammatory processes in human body. In the current healthcare, determination of TNFα blood or plasma level is done by Enzyme Linked Immuno-Sorbent Assay (ELISA) as a primary choice method. Piezoelectric immunosensors are analytical platform recording affinity interactions on their surface. It is inferred that the immunosensors would be a functional alternative to the ELISA. In this study, antibody against TNFα was immobilized on Quartz Crystal Microbalance (QCM) sensor and the same was made on magnetic particles. Human TNFα was measured in a way of interaction with QCM surface and then the particles were applied. The assay exerted sufficient limit of detection equal to 1.62pg/ml and it also fully correlated with standard ELISA tests. No interference by interleukin 6 or albumin was observed. Long term stability of the immunosensors lasting for at least three months was found. The immunosensors appears to be readily for practical performance and it would be an alternative to the standard ELISA especially when diagnoses made in field, homecare conditions or conditions of small hospitals as an emergency test.
Keywords: Humans; zlato; Quartz Crystal Microbalance Techniques; Biosensing Techniques; Antibody; Electricity; Affinity; ELISA; Inflammation; lidé; Piezoelectric; biosenzitivní techniky; Immunochemistry; Enzyme-Linked Immunosorbent Assay; TNF-alfa; Label free assay; TNFα; mikrorovnovážné techniky křemenného krystalu; Tumor Necrosis Factor-alpha; Biorecognition; Gold; elektřina; Quartz crystal microbalance; Biosensor